2020
DOI: 10.1128/aem.03015-19
|View full text |Cite
|
Sign up to set email alerts
|

Laccaria bicolor Mobilizes both Labile Aluminum and Inorganic Phosphate in Rhizosphere Soil of Pinus massoniana Seedlings Field Grown in a Yellow Acidic Soil

Abstract: Plant growth is often limited by highly activated aluminum (Al) and low available phosphorus (P) in acidic soil. Ectomycorrhizal (ECM) fungi can improve their host plants’ Al tolerance by increasing P availability while decreasing Al activity in vitro or in hydroponic or sand culture systems. However, the effect of ECM fungi on inorganic P (IP) and labile Al in acidic soil in the field, particularly in conjunction with Al treatment, remains poorly understood. The present study aimed to determine the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The growth of shoots but not roots of P. strobus seedlings growing in sand treated with 0-100 mg L -1 Al at pH 3.8 was also significantly improved by P. tinctorius (Schier and McQuattie 1995). Other studies (Gu et al 2019(Gu et al , 2020 showed that ECM fungus mobilized inorganic P in rhizosphere soil and facilitated nutrient uptake and transport; thus, both of the fungal species tested in the present study might have similar effects on nutrient mobilization and transport, which improved P. massoniana seedlings' aboveground growth.…”
Section: Al Tolerance In Seedlings With Ecmmentioning
confidence: 91%
“…The growth of shoots but not roots of P. strobus seedlings growing in sand treated with 0-100 mg L -1 Al at pH 3.8 was also significantly improved by P. tinctorius (Schier and McQuattie 1995). Other studies (Gu et al 2019(Gu et al , 2020 showed that ECM fungus mobilized inorganic P in rhizosphere soil and facilitated nutrient uptake and transport; thus, both of the fungal species tested in the present study might have similar effects on nutrient mobilization and transport, which improved P. massoniana seedlings' aboveground growth.…”
Section: Al Tolerance In Seedlings With Ecmmentioning
confidence: 91%
“…Recent studies have revealed that different species of plants, or even different plant traits of the same species, assemble different rhizosphere microbial communities in the same soil environment (Arafat et al, 2017;Sayer et al, 2017;Bickford et al, 2020). These complex plant-associated microbial communities are crucial for plants because they can affect plant growth, productivity, nutrients and immunity directly or indirectly (Van Wees et al, 2004;Egamberdieva et al, 2010;Erturk et al, 2010;Berendsen et al, 2012;Patel, 2018;Tahir et al, 2019;Gu et al, 2020;Song Q. et al, 2021), as well as affect host phenotypes and adaptability (Herrera Paredes et al, 2018). For instance, Finkel et al (2020) found that rhizosphere microorganisms can promote root growth by affecting plant hormone levels in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum can also combine with root cell membrane proteins, thereby causing cell membrane damage (Víctor et al, 2006;Gu et al, 2023). The portion of aluminum that enters the root cells directly affects cellular metabolism by inhibiting the absorption of nutrients such as calcium, phosphorus, and potassium (Gu et al, 2020). At present, it is still unknown which locations within the vertical structure of Masson pine forests are most severely affected by acid rainfall.…”
mentioning
confidence: 99%